Predictors for Selection of Insurance‐Funded Weight Loss Approaches in Individuals With Severe Obesity. (9th May 2015) - Matthews‐Ewald, Molly R.; Myers, Valerie H.; Newton, Robert L.; Beyl, Robbie; Waldo, Krystal; Dufour, Cody M.; Donato, Sheletta G.; Champagne, Catherine M.; Church, Timothy; Ryan, Donna H.; Brantley, Phillip J.
<x xml:space="preserve">Abstract</x> Objective To determine whether there are differences in baseline psychological and behavioral characteristics between individuals with severe obesity who chose a surgical or nonsurgical intervention for weight loss. Methods The current study utilized data from a larger study funded by a state insurance company and is unique in that the insurance company funded the weight loss interventions. Participants indicated their preferred method of weight loss, and completed several self‐report psychological questionnaires, as well as demographic information. Results Participants (N = 605) were 58.8% Caucasian and mostly (86%) female. Logistic regression results indicated that an increased number of weight loss attempts, and select other measures of eating behavior and quality of life may influence individuals' selection for either surgical or nonsurgical treatments for weight loss. Conclusions Practitioners should pay particular attention to these baseline characteristics that influence choice to examine potential characteristics that may influence the success of these weight loss treatments.